215 Postoperative Stereotactic Radiosurgery vs Observation for Completely Resected Brain Metastases: Results of a Prospective Randomized Study. (August 2016) - Rao, Ganesh; Ahmed, Salmaan; Hess, Kenneth; Mahajan, Anita
Abstract : INTRODUCTION: Stereotactic radiosurgery to a surgical cavity (SRS-cav) to improve local control (LC) after resection of brain metastases (BM) is an alternative to adjuvant whole brain radiotherapy (WBRT). There is limited prospective data regarding efficacy of SRS-cav for LC. METHODS: Patients with 1 to 3 BMs with complete resection of at least one were randomly assigned to SRS-cav or observation (OBS) of the cavity(ies). We stratified by number of BMs, histology, and volume. Unresected BMs were treated with SRS. The primary end point was failure of LC. Secondary end points included overall survival (OS), distant BM (DBM), complications, and WBRT. The study was designed with 80% power to detect a hazards ratio (HR) of 0.6 assuming a 2-sided 5% α and 50% LC at 6 months in the OBS arm. RESULTS: From October 2009 to October 2015, 131 patients with 140 resected BMs were randomly assigned to SRS-cav (n = 64) or OBS (n = 67). Thirty-four and 28 additional BMs were treated in the SRS-cav and OBS arms, respectively. Median follow-up was 12.6 months (range 0.3-70.6 months). LC rates were superior in the SRS-cav group (HR, 0.46; 95% confidence interval [CI], 0.25-0.85, P = .011). LC rates for SRS-cav and OBS were 83% vs 57% at 6 months and 72% vs 45% at 12 months, respectively. No significant SRS-cav complications were noted. DBM rate at 12 months was 43% vs 33% in the SRS-cav vs OBS groups, respectively, (HR, 0.79; 95% CI, 0.50-1.24, P = .29). Twenty-four SRS-cav and 30 OBS patients required WBRT (median time to WBRT of 16.1 and 15.2 months, respectively, HR, 0.8; 95% CI, 0.5-1.4, P = .42). Median OS was 17 months in both arms (HR, 1.22; 95% CI, 0.79-1.87, P = .37). On multivariate analysis, histology, lesion number, systemic disease status, or GPA did not affect LC. Use of SRS-cav (HR, 0.4; 95% CI, 0.2-0.8) was associated with better LC and preoperative tumor >3 cm (HR, 2.4; 95% CI, 1.2-4.9) was associated with worse LC. CONCLUSION: SRS to a surgical cavity improves LC compared with observation alone for BM. OS and DBM were not affected by the use of SRS.